Comparison of respiratory-triggered 3D MR cholangiopancreatography and breath-hold compressed-sensing 3D MR cholangiopancreatography at 1.5 T and 3 T and impact of individual factors on image quality. Issue 142 (September 2021) - Blaise, Hélène; Remen, Thomas; Ambarki, Khalid; Weiland, Elisabeth; Kuehn, Bernd; Orry, Xavier; Laurent, Valérie
Highlights: At 3 T, BH-CS-MRCP offers better image quality than conventional acquisition with respiratory-triggering. At 1.5 T, aside from sharpness, BH-CS-MRCP does not improve image quality. At 3 T image quality is not affected by individual patient characteristics. At 1.5 T, ascites on BH-CS-MRCP and high BMI on STD-MRCP are associated with degradation of image quality. Abstract: Purpose: To evaluate the image quality of an accelerated compressed-sensing single-breath-hold 3D magnetic resonance cholangiopancreatography (BH-CS-MRCP) prototype sequence compared to the standard 3D sequence with respiratory triggering (STD-MRCP) at 1.5 T and 3 T. To assess the individual factors that can affect image quality. Method: This is a retrospective analysis. Both sequences (BH-CS-MRCP and STD-MRCP) were performed in 200 patients at 1.5 T and 200 patients at 3 T. Overall image quality and the visualization of the bilio-pancreatic ducts were rated on a 5-point scale. Image sharpness and background suppression were rated on a 4-point scale. A double reading was performed in 50 patients to assess the inter-observer reproducibility. Individual characteristics studied were gender, age, BMI, ascites, abdominal surface and breath-hold quality. Results: At 1.5 T, BH-CS-MRCP was inferior to STD-MRCP in terms of overall quality (p = 0.0046), background suppression (p < 0.0001), visualization of the cystic duct (p < 0.0001), the right bile duct (p = 0.0008), the left bile duct (p = 0.0152), and the main pancreatic duct (p < 0.0001). However, BH-CS-MRCP was sharper than STD-MRCP (p = 0.028). At 3 T, BH-CS-MRCP was superior to STD-MRCP for overall quality (p < 0.0001), sharpness (p < 0.0001), and visualization of the bilio-pancreatic ducts (p < 0.0001). Background signal was conversely better suppressed in STD-MRCP (p < 0.0001). At 1.5 T, the volume of ascites was inversely correlated with image quality for BH-CS-MRCP while BMI was inversely correlated with image quality for STD-MRCP. Breath-hold quality was correlated with image quality for BH-CS-MRCP at 1.5 T and 3 T. Conclusion: BH-CS-MRCP is feasible in clinical routine at 1.5 and 3 T, yielding significantly better perceived image quality at 3 T but not at 1.5 T. BH-CS-MRCP appears to be influenced by ascites whereas STD-MRCP is influenced by BMI at 1.5 T. This study was approved by the Ethics Review Board for Research in Medical Imaging (IRB: CRM-2003–065).